The method of controlling the frequency of piezoelectric oscillators and filters using the direct control of the resonator - Hutornenko, Sergey; Semenets, Dmitry; Vasilchuk, Dmitry (Видавництво Львівської політехніки, 2012)
This paper presents methods of direct frequency control of generation radio equipment and the signals selection devices by means of direct effect on the piezoelectric element.
Keywords: the self-excited oscillator; the filter; the piezoelectric resonator; an interelectrode gap; a graded-index field